Managing Bahiagrass in Bermudagrass and Stargrass Pastures - Brent A. Sellers; Jason A. Ferrell (EDIS)
Revised! SS-AGR-257, a 4-page illustrated fact sheet by B. A. Sellers and J. A. Ferrell, describes how to prevent encroachment by bahiagrass into bermudagrass and stargrass pastures in Florida, and provides recommendations for chemical control, the impact of herbicide applications, and how to reduce forage-yield loss. Published by the UF Department of Agronomy, November 2009.